Impact of Intermittent Fasting on Lipid Profile–A Quasi-Randomized Clinical Trial - Ahmed, Naseer; Farooq, Javeria; Siddiqi, Hasan Salman; Meo, Sultan Ayoub; Kulsoom, Bibi; Laghari, Abid H.; Jamshed, Humaira; Pasha, Farooq (Frontiers in Nutrition, 2021)
Background: Sub-optimal HDL is a prognostic marker and a risk factor of cardiovascular disease. South Asia has a disproportionally high prevalence of sub-optimal HDL. Intermittent fasting (IF) is a type of energy restriction that may have beneficial impact on HDL levels including other lipid parameters and reduce the risk of cardiovascular diseases. Objective: The aim of the study was to evaluate the effect of intermittent fasting on lipid profile and HDL-cholesterol. Methods: Quasi-experimental type clinical trial was conducted on individuals with HDL < 40 mg/dl for men and < 50mg/dl for women for 6 weeks. The control group continued with their usual diet, while the intervention group fasted for 12 hours, three time per week for 6 weeks. Individual’s vitals including pulse rate and blood pressure, weight, waist circumference, serum lipid profile and blood glucose levels were measured at baseline and post study. Result: From the total of 40 enrolled participants according to inclusion criteria depending on HDL level, 20 volunteered to be in intervention group, other 20 allocated in control. The intervention group participants showed statically significant reduction of around 3.5 kg in body weight and 0.9 cm in waist circumference (p value= 0.0001). The intervention group showed an increase of 3 mg/dl (p value= 0.0001) in the level of HDL-C and reduction of 15.9mg/dl (p value=0.002) in the level of total cholesterol in comparison with baseline levels. Conclusion: This study suggested that intermittent fasting shows positive impact on cardiovascular health by improving the lipid profile particularly HDL. Intermittent fasting can be added in the daily life to maintain a healthy and balanced life style.